Lignocaine in Migraine Treatment: A Comprehensive Review - Kalisiak, Jakub; Tschuschke, Max; Choinka, Martyna; Lorenz, Mikołaj; Lewandowski, Jędrzej; Konopka, Agata; Szczepaniak, Zuzanna; Wdowiak, Natalia; Komarów, Małgorzata; Karasińska, Dominika (Quality in Sport, 2024)
Introduction: Migraine is a prevalent and debilitating neurological disorder characterized by recurrent headaches and associated symptoms such as nausea, photophobia, and phonophobia. While conventional treatments exist, a significant subset of patients suffers from refractory migraines, prompting the exploration of alternative therapies like lignocaine. Purpose of the work: This review examines the mechanisms by which lignocaine modulatespain and underscores the potential of lignocaine as a therapeutic option for refractory migraines, while also highlighting the need for continued research to refine its clinical application. Materials and methods: A comprehensive analysis of research papers available on PubMed, Google Scholar, Web of Science, Embase and Scopus was undertaken using the searchterms encompassing the following keywords: chronic migraine / lignocaine migraine / migraine treatment/ migraine pain mechanism / migraine chronic pain mechanism / lignocaine and ketamine migraine / lignocaine adverse effects / lignocaine safety / refractory migraine. Results: Lignocainehas shown promise in alleviating both acute and chronic migraine pain. However, its use requires careful patient selection and monitoring due to potential side effects, such as cardiac and central nervous system toxicity. Despite these risks, the favorable safety profile and efficacy of lignocaine make it a valuable option in migraine management. Future research should focus on optimizing dosing protocols, evaluating long-term outcomes, and identifying biomarkers to guide patient selection.